A Qualitative Service Evaluation Exploring Staff Nurses Views and Perceptions of Using a Paperless System in an Intensive Care Unit - Williamson, Hannah (2011)
Technology is vital within the healthcare environment, and is especially essential in Intensive Care Units which care for the most critically ill patients. Over the last decade there has been an increasing pressure on hospitals to use this technology to reduce the amount of paper and to save resources. As a result, systems such as EMRs, CPOEs and PDMSs are being increasing implemented within health care settings. However, despite this increase in technology implementation, there is a lack of research into the user’s views on such systems, in particular PDMS. This evaluation aims to gain an insight into staff nurse’s views and perceptions of using a PDMS system in an intensive care unit and explore how much of an impact it has had on their way of working. Eleven staff nurses working on the unit were interviewed using a semi-structured format and these interviews were then transcribed and analysed using the thematic approach. The findings show that in general the staff nurses were extremely positive when discussing the paperless system, with aspects such as nurse – nurse communication, patient care and safety being seen as having improved since the implementation. Many also found the increased amount of information and the ease in which data can be accessed to be key advantages to the system. However, doctor – nurse communication, discharges and system break downs were cited as major problems. These findings are generally supported by existing literature. The evaluation considers it limitations and whilst generalisability is difficult, this evaluation can be seen as making a valuable contribution to the topic area and for the unit involved in the study. It is recommended that further research involving multiple units or wards still needs to be carried out in order to fully explore the use of PDMS systems in hospitals.